(untitled) (Al-Qamar, 2021)
By its very nature, human behavior remains complex, which is also governed by subtle aspects of the situation or context in which they are embedded. Certain negative factors develop radical behaviorism, and these factors are the essential tasks to understand the behavioral changes in a particular environmental domain due to which radical behaviorism tends towards extremism. Sometimes this extremism leads towards terrorism which is not acceptable in any society. A person does not become radical within a day, and it is a slow and gradual process that requires a progression through distinct stages that happens nor quickly nor easily. Radicalized minds start violating laws in society that badly hit their surroundings. Most communities and individuals become resilient for Radicalization due to the exploitation of fundamental rights, undue imbalances in society, class differences, poor socio-political structure, and high illiteracy rate provide evidence to the factors shaping social practices and behaviorism. This paper focuses on radical behaviorism in Pakistan, and four types of behaviorism will be discussed here that drive balanced behaviorism towards radical behaviorism. Radical behaviorism is the problem of Pakistan, but it is a global problem, and internal and external factors are involved that spoil the thinking track of particular groups of people, especially those who are considered the most sensitive group of people. Radicalization is the opposite of pluralism that may be expressed by nonviolent density in actions that deviate from the norms and show disapproval for the present domain of life and environment.